2016
DOI: 10.1126/science.aaf6116
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus impairs growth in human neurospheres and brain organoids

Abstract: Since the emergence of Zika virus (ZIKV), reports of microcephaly have increased considerably in Brazil; however, causality between the viral epidemic and malformations in fetal brains needs further confirmation. We examined the effects of ZIKV infection in human neural stem cells growing as neurospheres and brain organoids. Using immunocytochemistry and electron microscopy, we showed that ZIKV targets human brain cells, reducing their viability and growth as neurospheres and brain organoids. These results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
618
1
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,036 publications
(696 citation statements)
references
References 27 publications
34
618
1
11
Order By: Relevance
“…This was possibly because the African lineage strain of ZIKV was associated with low viremia in humans [77], whereas the Asian lineage strain of ZIKV, involved in current outbreaks (Pacific Islands and in South America), is spreading along long chains of human-to-human transmissions. Second, the differences between the genetic makeup of the African and Asian lineages and adaptive changes in the Brazilian strain might explain the recent emergence of ZIKV-associated complications in humans [78][79][80]. Third, microcephaly is a rare disease and has many causes [81] other than ZIKV.…”
Section: Intrauterine (Congenital) Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was possibly because the African lineage strain of ZIKV was associated with low viremia in humans [77], whereas the Asian lineage strain of ZIKV, involved in current outbreaks (Pacific Islands and in South America), is spreading along long chains of human-to-human transmissions. Second, the differences between the genetic makeup of the African and Asian lineages and adaptive changes in the Brazilian strain might explain the recent emergence of ZIKV-associated complications in humans [78][79][80]. Third, microcephaly is a rare disease and has many causes [81] other than ZIKV.…”
Section: Intrauterine (Congenital) Infectionmentioning
confidence: 99%
“…Recently, a few studies [79,80,[82][83][84][85] have evidenced the pathogenic potential of Brazilian strain of ZIKV during the development of fetus in animal models. These studies concluded that ZIKV first infects the placenta and then the brain of fetus, where it preferentially infects neural progenitor cells and decreases their viability and growth as neurospheres through down-regulation of genes that are involved in cell and organ development, and up-regulation of genes that are involved in immune responses.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
“…These studies have provided evidence that human neural stem cells are selectively vulnerable35, 48 and more susceptible to premature differentiation50 upon Zika virus infection, providing a molecular explanation for the observed microcephaly. A further study suggested activation of innate immune responses as a possible mechanism for Zika‐induced neuroprogenitor cell death 47.…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 95%
“…Several research groups applied the brain organoid model to study Zika infection, a current epidemic that has been strongly linked to newborn microcephaly 35, 46, 47, 48, 49, 50. These studies have provided evidence that human neural stem cells are selectively vulnerable35, 48 and more susceptible to premature differentiation50 upon Zika virus infection, providing a molecular explanation for the observed microcephaly.…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 99%
“…ZIKV invades fetal neural progenitor cells and causes brain abnormalities by at least two general mechanisms: (1) direct destruction of neuronal progenitor cells and developing neurons, and (2) disruption of the differentiation, development, and migration of neurons in the developing brain (Garcez et al, 2016; Qian et al, 2016; Sarno et al, 2016; Tang et al, 2016; Cugola et al, 2016; Li et al, 2016). Both the Brazilian ZIKV strain and the Asian ZIKV strain cause abnormal cortical development in mice (Cugola et al, 2016; Li et al, 2016) that would be consistent with multiple different types of cortical malformations in human infants exposed in utero to ZIKV among both those with congenital microcephaly and those with normal head circumferences at birth.…”
Section: In Utero Zika Virus Infection Congenital Microcephaly and mentioning
confidence: 99%